Smoking knowledge and decision in an era of widespread awareness: Persistent disparities and policy implications - Miguel Antonio Garcia Estrada; Rutcher Madera Lacaza; Kent Jason Go Cheng (PLoS ONE, 2025)
Years of anti-smoking campaigns to promote public awareness about smoking’s negative health effects have resulted in increased awareness across a large segment of the population. Amid gains in smoking-related knowledge, important but unexplored questions remain about population-level trends and the continuing importance of knowledge-based anti-smoking policies. Using the Philippine case, this paper is the first to examine persistent disparities in knowledge on smoking’s health risks and the continued importance of knowledge-based interventions in discouraging smoking. We also investigated whether knowledge moderates the effect of price on smoking decisions. For this cross-sectional study, we conducted ANOVA, Tukey HSD tests, and a two-part multivariate regression model on the 2009, 2015, and 2021 waves of the Philippine Global Adult Tobacco Survey. We used daily cigarette sticks smoked as the dependent variable and (a) a binary and discrete variable measuring smoking health risk, (b) a categorical variable for wealth quintile, and (c) an interaction term as the main independent variables. We found that knowledge on smoking’s ill health effects, by itself, continues to be negatively associated with smoking, even as 9 out of 10 individuals already possess knowledge about smoking’s health risks. Individuals who view smoking as addictive and as having ill health effects smoke 1 stick (10.8% of average sticks) less. Persistent disparities in knowledge between the lowest and highest wealth groups were observed. Despite significant gains in population-wide smoking-related knowledge, disparities across socioeconomic groups persist. Closing knowledge-based disparities calls for approaches that are tailored to the needs of different groups, particularly less affluent individuals.